A note on Fibonacci matrices of even degree - Michele Elia (International Journal of Mathematics and Mathematical Sciences)
This paper presents a construction of m-by-m irreducible Fibonacci matrices for any even m. The proposed technique relies on matrix representations of algebraic number fields which are an extension of the golden section field. The explicit construction of some 6-by-6 and 8-by-8 irreducible Fibonacci matrices is given.